Assessing Knowledge, Attitude and Practice Toward Prostate Cancer Among Males at Seiyun University, Hadramout, Yemen: KAP study of Prostate Cancer Among Males at Seiyun University, - Hassan Pyar Hassan; Sarah Omer Al-Sawmhi; Samaher E. BaGais; Muna A. Mugibel (NERS Jurnal Keperawatan, 2025)
Prostate cancer remains a major global health challenge, recognized as the second most prevalent cancer among men and the fifth leading cause of mortality worldwide. This study aimed to evaluate the current knowledge, attitudes and practices regarding prostate cancer. An analytical, cross-sectional survey was conducted among 326 adult males at Seiyun University, Yemen. Data were collected using a validated, self-administered questionnaire that covered sociodemographic, family history, awareness, symptoms' knowledge, risk factors, attitudes and screening practices. Ethical approval and verbal informed consent were obtained. Descriptive statistics, KAP categorization, and chi-square were performed. Overall, participants demonstrated limited awareness with 25% having heard of prostate cancer and 6% aware of specific screening programs. The majority (69%) correctly identified blood tests as the best screening method, only 17% knew the appropriate age for screening. Interestingly, only 1.2% of participants reported having been screened for prostate cancer. Meanwhile, 6% indicated a family history of cancer, mostly breast cancer in second-degree relatives. The study found significant correlations between participants' knowledge levels, age, and the type of college attended. Importantly, there was a significant association between having a family history of cancer and undergoing screening procedures. In other words, participants with a family history of cancer were more likely to participate in screening practices. This study highlights a significant deficit in prostate cancer knowledge and alarmingly low screening rates. The findings underscore an urgent need for comprehensive, culturally sensitive, and evidence-based educational initiatives in Yemen. These efforts should specifically target identified knowledge gaps related to symptoms, risk factors, and appropriate screening age, and be tailored to specific age groups and college types, leveraging the influence of family history, to foster proactive health behaviors and improve early detection.